Quantity and quality of interaction between staff and older patients in UK hospital wards: A descriptive study. (October 2016) - Barker, Hannah Ruth; Griffiths, Peter; Mesa-Eguiagaray, Ines; Pickering, Ruth; Gould, Lisa; Bridges, Jackie
Abstract: Background: The quality of staff-patient interactions underpins the overall quality of patient experience and can affect other important outcomes. However no studies have been identified that comprehensively explore both the quality and quantity of interactions in general hospital settings. Aims & objectives: To quantify and characterise the quality of staff-patient interactions and to identify factors associated with negative interaction ratings. Setting: Data were gathered at two acute English NHS hospitals between March and April 2015. Six wards for adult patients participated including medicine for older people (n = 4), urology (n = 1) and orthopaedics (n = 1). Methods: Eligible patients on participating wards were randomly selected for observation. Staff-patient interactions were observed using the Quality of Interactions Schedule. 120 h of care were observed with each 2 h observation session determined from a balanced random schedule (Monday-Friday, 08:00-22:00 h). Multilevel logistic regression models were used to determine factors associated with negative interactions. Results: 1554 interactions involving 133 patients were observed. The median length of interaction was 36 s with a mean of 6 interactions per patient per hour. Seventy three percent of interactions were categorized as positive, 17% neutral and 10% negative. Forty percent of patients had at least one negative interaction (95% confidence interval 32% to 49%). Interactions initiated by the patient (adjusted Odds Ratio [OR] 5.30), one way communication (adjusted OR 10.70), involving two or more staff (adjusted OR 5.86 for 2 staff, 6.46 for 3+ staff), having a higher total number of interactions (adjusted OR 1.09 per unit increase), and specific types of interaction content were associated with increased odds of negative interaction (p < 0.05). In the full multivariable model there was no significant association with staff characteristics, skill mix or staffing levels. Patient agitation at the outset of interaction was associated with increased odds of negative interaction in a reduced model. There was no significant association with gender, age or cognitive impairment. There was substantially more variation at ward level (variance component 1.76) and observation session level (3.49) than at patient level (0.09). Conclusion: These findings present a unique insight into the quality and quantity of staff-patient interactions in acute care. While a high proportion of interactions were positive, findings indicate that there is scope for improvement. Future research should focus on further exploring factors associated with negative interactions, such as workload and ward culture.